Different Version, Similar Result? A Critical Analysis of the Multiplicity of Shortened Versions of the Zimbardo Time Perspective Inventory. (May 2020) - Perry, John L.; Temple, Elizabeth C.; Worrell, Frank C.; Zivkovic, Urška; Mello, Zena R.; Musil, Bojan; Cole, Jon C.; McKay, Michael T.
The Zimbardo Time Perspective Inventory (ZTPI) has been extensively used, with more than 1, 400 citations in Scopus alone. After identifying psychometric problems however, several authors have attempted to overcome limitations by shortening the scale. As such, there now exist multiple. shortened versions of the ZTPI, all using some of the original 56 items. Although each shorter version reports various broadly acceptable validity parameters using the group with which it was developed, these are often sample specific and at the cost of reliability, generalizability, and ability to detect individual differences in the construct. To examine this more closely, we reviewed the psychometric properties of the ZTPI and some of its derivatives, and found that data-driven approaches to creating these shortened versions of the scale prioritized improved model fit over internal reliability and sensitivity. In conclusion, we suggest that it is time for a new collaborative strategy to address conceptual and measurement concerns with the ZTPI, and discourage data-driven and sample-specific solutions to the psychometric concerns of the scale's scores. More broadly, we recommend that researchers consider the impact on reliability, generalizability, and ability to detect individual differences when developing short psychometric scales.